The Reaction Of Female Consumer In Klang Valley For The Age Group 15 To 25 Years Old Towards The Products Endorsed By Celebrities - Oh, Vincent Kim Seng (2006)
Today companies choose to utilize celebrity as endorsers in their marketing campaigns. The purpose of this research project is to gain a deeper understanding of the degree of influence that a celebrity wields on the female consumers.